KEY DETERMINANTS OF USING DERIVATIVE INSTRUMENTS IN THE USA - Ladha, Vedant Surendrakumar (2018)
This piece of work attempts to distinguish among various theories of corporate hedging with the help of disclosure in 10-K or annual reports of 500 non-financial USA companies and collecting data manually about hedging activities. There is rather limited but growing use of derivative financial instrument for risk management currently. Modern financial theories predict some characteristics of firms that drive their decision to use derivative financial instrument or off-balance sheet transaction. In this work, empirical evidence on determinants of derivative instruments usage is provided with large sample of the USA’s non-financial firms. S&P 500 and 600 companies are chosen to be the initial sample size of this research. Centered on the evidence, author draws the followings conclusions. Both tax incentives and financial price exposure are directly related with the decision of whether firm’s use of derivatives instrument. Moreover, the probability of using derivatives is directly proportional with leverage & firm value on the one hand. On the other hand, the level of using derivatives is positively correlated with dividend payout. These findings in the studies are generally in line with previous theories except for market-to-book ratio which is used to represent growth opportunities is negatively associated rather positively associated with the usage of derivative financial instruments. Keywords: Derivatives, corporate hedging, risk management strategies, underinvestment cost and cost of financial distress.